Atomic magnetometers and their application in industry - Bai, Xuanyao; Wen, Kailun; Peng, Donghong; Liu, Shuangqiang; Luo, Le (Frontiers in Physics, 2023)
In modern detection techniques, high-precision magnetic field detection plays a crucial role. Atomic magnetometers stand out among other devices due to their high sensitivity, large detection range, low power consumption, high sampling rate, continuous gradient measurements, and good confidentiality. Atomic magnetometers have become a hot topic in the field of magnetometry due to their ability to measure not only the total strength of the Earth's magnetic field, but also its gradients, both slow- and high-velocity transient magnetic fields, both strong and weak. In recent years, researchers have shifted their focus from improving the performance of atomic magnetometers to utilizing their exceptional capabilities for practical applications. The objective of this study is to explore the measurement principle and detection method of atomic magnetometers，and it also examines the technological means and research progress of atomic magnetometers in various industrial fields, including magnetic imaging, material examination, underwater magnetic target detection, and magnetic communication. Additionally, this study discusses the potential applications and future development trends of atomic magnetometers.